Rhein protects against renal aging and fibrotic injury by multiple targets through inhibition of TNF-α-mediated autophagy and necroptosis crosstalk - Tu, Yue; Liu, Wenjie; Sang, Tianqing; Pan, Liuyunxin; Wu, Wei; Fang, Qijun; Liu, Yinglu; Liu, Buhui; Wan, Yigang (Frontiers in Pharmacology, 2026)
IntroductionRhein, an anthraquinone derived from rhubarb, exhibits renoprotective effects in aging and kidney injury; however, the mechanistic interplay with TNF-α-mediated cell death pathways remains undefined.MethodsUsing D-galactose (D-gal)-treated NRK-52E cells and aged rats, we assessed rhein’s effects with/without mTOR regulators (rapamycin/MHY1485) or etanercept (TNF-α inhibitor). Protein levels of klotho, phosphorylated (p)-mTOR, p-p62, caspase-8, beclin1, light chain 3 II, receptor-interacting protein kinase (RIPK)1, RIPK3, and p-mixed lineage kinase-like (MLKL) were measured. The concentration of reactive oxygen species (ROS) and the staining for senescence-associated-β-galactosidase (SA-β-gal) were also assessed. The network framework of “rhein–target–pathways” was identified. Additionally, serum untargeted metabolomics and KEGG pathway analysis were performed to identify altered metabolites and underlying metabolic pathways.ResultsThe results indicated that rhein increased the protein levels of klotho, p-mTOR, p-p62, and caspase-8, as well as decreased the concentration of ROS, the staining for SA-β-gal, and the protein levels of beclin1, light chain 3 II, RIPK1, RIPK3, and p-MLKL in NRK-52E cells exposed to D-gal. Compared to mTOR regulators (rapamycin or MHY1485) alone, the co-treatment of rhein and mTOR regulators decreased mTOR-mediated autophagy signaling in NRK-52E cells treated by D-gal. In addition, rhein decreased tumor necrosis factor (TNF)-α and TNF-α receptor1 protein levels. Interestingly, the effects of etanercept in TNF-α-mediated necroptosis and autophagy were similar to those of rhein. Consistent with the in vitro findings, rhein alleviated oxidative stress and exerted renal protective effects in aged model rats. Serum untargeted metabolomic analysis revealed that rhein treatment significantly altered 85 metabolites compared to the model group rats, with 35 metabolites upregulated and 50 downregulated. KEGG pathway analysis identified the TNF-α signaling pathway as a key metabolic pathway involved.DiscussionIn conclusion, rhein protected the kidneys by activating p-mTOR and downregulating TNF-α, necroptosis and autophagy. Rhein mitigates renal aging and fibrotic injury by targeting TNF-α-mediated autophagy-necroptosis crosstalk, positioning it as a novel multi-target therapeutic agent for age-related kidney injury.